Effect of power density on compositional and structural evolution of ITO thin film by HiPIMS method. (June 2022) - Zhao, Ming-Jie; Zhang, Jin-Fa; Huang, Jie; Huang, Qi-Hui; Wu, Wan-Yu; Tseng, Ming-Chun; Huang, Chien-Jung; Kuo, Hao-Chung; Lien, Shui-Yang; Zhu, Wen-Zhang
Abstract: Tin doped indium oxide (ITO) film was prepared by high power impulse magnetron sputtering. The effects of power density on the compositional and structural evolution of the film were investigated. The higher power density was found to increase the Sn/In ratio due to the weakening of self-sputtering effect as the initial energy of sputtered species increases. The higher excitation/ionization rate of the oxygen species in the plasma at higher power density was found effective for passivating the oxygen vacancy defects and raising the Sn doping efficiency in ITO film. In addition, The higher power density also leads to the change of (2 2 2)-orientated grains to (4 0 0)-orientated grains, which is possibly due to the reduction of diffusion length and rising migration barrier of the deposited cations by increasing number of oxygen radicals. As the power density increases, the carrier concentration increases due to higher Sn content and Sn doping efficiency. The carrier mobility increases due to the crystal orientation change, passivation of oxygen vacancy defects and larger grain size. ITO film with resistivity of 4.1 × 10 −3 Ω cm and transmittance of over 78% at 400–800 nm was obtained at a power density of 1.30 W/cm 2 . Highlights: ITO films are prepared by in-line high power impulse magnetron sputtering (HiPIMS) at room temperature. An increase of Sn content and doping efficiency were observed as the average power increases at 0.52–1.56 W/cm 2 . The crystal orientation of the film changes from (2 2 2) to (4 0 0) with increasing power density as observed by XRD. The (4 0 0) orientated film has better electrical properties and rougher surface. ITO film deposited at 1.30 W/cm 2 has a low resistivity of 4.1 × 10 −3 Ω cm and a high transmittance of > 78% at 400–800 nm.